Novel Allosteric Mechanism of Dual p53/MDM2 and p53/MDM4 Inhibition by a Small Molecule - Grinkevich, Vera V.; Vema, Aparna; Fawkner, Karin; Issaeva, Natalia; Andreotti, Virginia; Dickinson, Eleanor R.; Hedström, Elisabeth; Spinnler, Clemens; Inga, Alberto; Larsson, Lars-Gunnar; Karlén, Anders; Wilhelm, Margareta; et al. (Frontiers in Molecular Biosciences, 2022)
Restoration of the p53 tumor suppressor for personalised cancer therapy is a promising strategy. However, high-affinity MDM2 inhibitors have shown substantial side effects in clinical trials. Thus, elucidation of the molecular mechanisms of action of p53 reactivating molecules with the alternative functional principle is of the utmost importance. Here, we report a discovery of a novel allosteric mechanism of p53 reactivation through targeting the p53 N-terminus which blocks both p53/MDM2 and p53/MDM4 interactions. Using biochemical assays and molecular docking, we identified the binding site of two p53 reactivating molecules, RITA and protoporphyrin IX (PpIX). Ion-mobility mass spectrometry revealed that the binding of RITA to serine 33 and serine 37 is responsible for inducing the allosteric shift in p53, which shields the MDM2 binding residues of p53 and prevents its interactions with MDM2 and MDM4. Our results point to an alternative mechanism of blocking p53 interaction with MDM2 and MDM4 and may pave the way for the development of novel allosteric inhibitors of p53/MDM2 and p53/MDM4 interactions.